Use of yeast artificial chromosome clones for mapping and walking within human chromosome segment 18q21.3. - Silverman, G A (1989)
Well-characterized large genomic clones obtained from yeast artificial chromosome (YAC) libraries provide the framework to localize genes and approach genetic disease. We developed universally applicable approaches to establish authenticity, localize and orient internal genes, map restriction sites, and rescue the distal ends of large human genomic DNA inserts. We selected human chromosome segment 18q21.3 as a model system. Molecular cloning of this segment was initiated by characterizing three plasminogen activator inhibitor type 2 (PAI-2) clones [290, 180, and 60 kilobases (kb)] isolated from a YAC library. Comparison of YAC and bacteriophage lambda genomic DNA clones confirmed the fidelity of the PAI-2 locus. Detailed rare cutting restriction maps were generated by ramped contour-clamped homogeneous electric field electrophoresis. The PAI-2 locus was located and oriented within the YACs, which span a distance 70 kb 5' to 220 kb 3' of PAI-2. Moreover, both left and right ends of the YAC genomic DNA inserts were rescued by amplifying circularized cloning sites with an inverted form of the polymerase chain reaction. These unique terminal genomic DNA fragments were used to rescreen the YAC library and isolate overlapping clones that extend the map. These approaches will enable neighboring loci to be definitively linked and establish the feasibility of using YAC technology to clone and map chromosomal segments.